The Representation of Gen Z Slang in Online News: A Critical Discourse Analysis of Kompas.Com - Gabriella Pardede; Heltri F Samongilailai; Ariel Jonivedi Silalahi; Partohap Saut Raja Sihombing (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study investigates the representation of Generation Z (Gen Z) slang in online news discourse by analyzing a Kompas.com article entitled “Bahasa Gaul Gen Z Kian Marak, Begini Kata Peneliti Bahasa” published on November 8, 2024. The research aims to reveal how Gen Z slang is constructed as a social phenomenon and how ideological meanings are embedded through media language. This study employs a descriptive qualitative method under a critical paradigm, using Norman Fairclough’s three-dimensional Critical Discourse Analysis (CDA) framework: textual analysis (micro level), discursive practice (meso level), and socio-cultural practice (macro level). The findings show that the article frames Gen Z slang as an increasingly widespread trend through evaluative lexical choices such as “kian marak” and the inclusion of popular terms like FOMO, YOLO, JOMO, healing, and ghosting. At the discursive practice level, Kompas.com legitimizes the phenomenon by combining Gen Z voices with expert commentary, creating a hierarchy of authority in which academic interpretation becomes dominant. At the socio-cultural level, the discourse reflects broader contexts of digital culture, globalization, and generational identity, while also revealing an ideological tension between viewing slang as linguistic creativity and treating it as an influence-driven trend that may challenge standard language norms. Overall, the study confirms that online news media plays an active role in shaping public perceptions of youth language, constructing Gen Z slang not only as a linguistic variation but also as a cultural marker tied to identity and power relations in contemporary Indonesian society